Analisis Faktor Konfirmatori Bauran Pemasaran Untuk Penciptaan Brand Image Pisang Mas Kirana (Musa Acuminate) Kabupaten Lumajang - Bagus Putu Yudhia Kurniawan (Universitas Airlangga, 2016)
Economic developments in Lumajang still based on agriculture sector. One of the major agricultural commodities in Lumajang with patented flagship product is the “Pisang Mas Kirana”. Characteristics of “Pisang Mas Kirana” is no different than other agricultural commodities, which is easily broken and consumed in a fresh state, so it needs special treatment in post-harvest handling and the right strategy for the marketing of “Pisang Mas Kirana” to be effective and efficient. One marketing strategy that is widely used is to analyze the marketing mix “Pisang Mas Kirana”. The purpose of this study was to determine the relationship of each indicator with the marketing mix variables that influence and contribute to the creation of the brand image of “Pisang Mas Kirana”, with the maximum likelihood estimation (MLE) method to estimate the model parameters. The analysis technique used in this study is a confirmatory factor analysis. The results showed that the perception of respondents study to the marketing mix and brand image “Pisang Mas Kirana” were good. Most powerful indicator as a measuring product variable was the color, while the weakest was the packaging. Most powerful indicator as a measure of price variables were price variations, while the weakest was the price of “Pisang Mas Kirana”. Most powerful indicator variable as a measure of the distribution channel was location, while the weakest was transportation. Most powerful indicator as a measure of promotion variable was the media of the promotion, while the weakest was clear information. Most powerful indicator variable as a measure of brand image was the image of the consumer, while the weakest were the image makers.